2022
DOI: 10.5109/4794167
|View full text |Cite
|
Sign up to set email alerts
|

The Release of Hydrogen from NaBH_4 with Ni-Cu-B/Hydroxyapatite as The Catalyst

Abstract: The environmentally friendly combustion of hydrogen makes hydrogen an ideal fuel. Research on the ideal hydrogen storage is still being carried out. one candidate for hydrogen storage is NaBH4. NaBH4 is hydrolyzed to release hydrogen. This work concerns the hydrolysis reaction of NaBH4 to release hydrogen with a catalyst Ni-Cu-B deposited on hydroxyapatite. The research went through 2 stages, namely catalyst synthesis and NaBH4 hydrolysis reaction. The catalyst synthesis was carried out electrochemically using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Lai et al [11] investigated in the literature the development of core@shell nanocomposites (NaBH 4 @Ni) by loading metallic nickel catalysts to promote hydrolysis directly onto NaBH 4 nanoparticles, and optimized the effective weight hydrogen storage of NaBH 4 @Ni nanoparticles by adjusting the amount of water required for hydrolysis, obtaining an effective hydrogen storage of 4.4 wt%. Experimental data show that the catalyst produces hydrogen from NaBH 4 hydrolysis at 60 ºC in the presence of excess water at a rate of up to 22.5 L min -1 g - Al [12], Ni-La-B [13], Ni-Cu-B [14], Ni/Al 2 O 3 [15], Ni 2 P-CoP [16] have also shown good properties. For example, Yu-Jin Lee et al [12] synthesized a new Ni-Al alloy catalyst by aluminizing nickel foam, post-annealing, and selective aluminum leaching.…”
Section: 1metal Catalystsmentioning
confidence: 96%
“…Lai et al [11] investigated in the literature the development of core@shell nanocomposites (NaBH 4 @Ni) by loading metallic nickel catalysts to promote hydrolysis directly onto NaBH 4 nanoparticles, and optimized the effective weight hydrogen storage of NaBH 4 @Ni nanoparticles by adjusting the amount of water required for hydrolysis, obtaining an effective hydrogen storage of 4.4 wt%. Experimental data show that the catalyst produces hydrogen from NaBH 4 hydrolysis at 60 ºC in the presence of excess water at a rate of up to 22.5 L min -1 g - Al [12], Ni-La-B [13], Ni-Cu-B [14], Ni/Al 2 O 3 [15], Ni 2 P-CoP [16] have also shown good properties. For example, Yu-Jin Lee et al [12] synthesized a new Ni-Al alloy catalyst by aluminizing nickel foam, post-annealing, and selective aluminum leaching.…”
Section: 1metal Catalystsmentioning
confidence: 96%
“…The use of Cu as a catalyst for this reaction has not been studied. The results showed that after the electrolysis process, hydrogen proved to be very effective as a combustible fuel 37) Makaryan et al ( 2022) highlights the development done in the field of methane-hydrogen mixtures used as a promising low carbon fuel in various energy applications. This study gives us a detailed review on the energy characteristics of hydrogen as well as methane-hydrogen mixtures.…”
Section: Adrian Et Al (2022)mentioning
confidence: 99%